Clinical utility of plasma Epstein‐Barr virus DNA and ERCC1 single nucleotide polymorphism in nasopharyngeal carcinoma. Issue 16 (6th May 2015) - Hui, Edwin P.; Ma, Brigette B. Y.; Chan, K. C. Allen; Chan, Charles M. L.; Wong, Cesar S. C.; To, Ka Fai; Chan, Anthony W. H.; Tung, Stewart Y.; Ng, Wai‐Tong; Cheng, Ashley C.; Lee, Victor H. F.; Chan, Stephen L.; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND Single nucleotide polymorphism (SNP) of the excision repair cross‐complementing group 1 (ERCC1) gene has been linked with sensitivity to platinum and radiation. The authors hypothesized that the ERCC1 genotype for the SNPs cytosine‐to‐thymine substitution at codon 118 (C118T) and cytosine‐to‐adenine substitution at codon 8092 (C8092A) is prognostic in patients with nasopharyngeal carcinoma (NPC) who receive either radiotherapy (RT) or cisplatin plus RT. METHODS The authors tested their hypothesis using biomarker screening samples from the Hong Kong NPC Study Group 0502 trial, which was a prospective, multicenter clinical trial that used post‐RT plasma Epstein‐Bar virus (EBV) DNA (pEBV) levels to screen patients with high‐risk NPC for adjuvant chemotherapy. RESULTS ERCC1 SNPs were analyzed in 576 consecutive patients who were screened by pEBV. In the total biomarker population, there was no significant association of ERCC1 C118T or C8092A genotype with relapse‐free survival (RFS) or overall survival (OS). There also was no correlation between ERCC1 genotype and ERCC1 protein or messenger RNA expression in a subset of patients who had available paired biopsies. Post‐RT pEBV status was the only independent prognosticator for RFS and OS in multivariate analyses. However, there was a significant interaction between ERCC1 C118T genotype and post‐RT pEBV status (RFS, P = .0106; OS, P = .0067). The ERCC1 C118T genotype was significantly associated with both RFS (hazard ratio, 1.67; 95% confidence interval, 1.07‐2.61; P = .024) and OS (hazard ratio, 2.31; 95% confidence interval, 1.22‐4.40; P = .0106) in the post‐RT pEBV‐negative population, but not in the pEBV‐positive population. CONCLUSIONS The current results prospectively validate pEBV as the most significant prognostic biomarker in NPC that can be used to select high‐risk patients for adjuvant therapy. The ERCC1 C118T genotype may help to identify a favorable subgroup (approximately 7%) of pEBV‐negative patients with NPC who have an excellent prognosis and can be spared the toxicities of further therapy. Cancer 2015;121:2720‐2729. © 2015 American Cancer Society